The 30-Minute Sprint: Recognizing Intrapartum Prematurity Counseling Limitations - Georgescu, Abigail; Muthusamy, Anbu; Basir, Mir A. (Journal of Pediatric Intensive Care, 2021)
Describe the characteristics and content of intrapartum counseling provided to women hospitalized for premature birth between 23 and 34 weeks' gestation age (GA). The study was conducted between April and December 2009 in two teaching hospitals with labor and delivery units and level 3 neonatal intensive care units. Counselors completed a postcounseling survey. From 60 sessions, 46 surveys were collected. The median counseling duration was 30 minutes; this was not associated with gestational age. The support-person was not present for most (57%) counseling sessions. There was a positive correlation (p = 0.001) between the number of maternal questions and her education. There was no difference in counseling content across the 23 to 34 weeks' GA regarding delivery room care, physical/mental disability, and vision problems. This study of characteristics and content of premature birth counseling for birth between 23 and 34 weeks' GA found that the duration of most sessions is 30 minutes; the father of the baby is not present during counseling for most premature births, and the topics discussed by counselors are fairly similar and extensive irrespective of the GA. These findings highlight the existing contrast between the recommended counseling practices and the actual practice reported by counselors.
Keywords: premature infant; premature birth; patient education; counseling; telemedicine